Arbitration in state investment contract disputes - ابراهيم يزن; سحر احمد طيبا; سلمان عثمان (Latakia University Journal - Economic and Legal Sciences Series, 2024)
State contracts concluded by states with foreign persons are among the important contracts for states , these contracts aim to achieve economic and social development for the state , there are many forms and types of these contracts , the most prominent of which are investment contracts International investment activities related to the movement of capital , goods , services and people across the national borders of different countries it creates a kind of difference in the legal system between the foreign investor and the countries hosting the investment disputes often arise between them , and arbitration is resorted to as a friendly and quick means of resolving disputes Arbitration has become a refuge for states and investors in the field of contracts concluded by states with foreign investors , as the presence of the state in the contract makes the investor need judicial guarantees to protect his investments due to considerations of sovereignty enjoyed by the state , which makes foreign investors suspicious of the impartiality of the national courts of the host state and the influence of the judge , with the prevailing ideology in his country